Temporal and spatial expression of caudal-type homeobox proteins in the midgut of human embryos - Tang, Xiao-Bing (Int J Clin Exp Med, 2015)
Background: This study aimed to determine the spatiotemporal expression of caudal-type homeobox genes (CDX1, CDX2 and CDX4) during development of the midgut in human embryos and to explore the possible roles of CDX genes during the morphogenesis of human midgut. Human embryos (n=28) were sectioned serially and sagittally and CDX1, CDX2 and CDX4 proteins were detected on the midline from the 5th to 9th weeks of gestation by immunohistochemical staining. Results: CDX1, CDX2 and CDX4 proteins were weakly expressed in epithelium and mesenchyme of the midgut in the 6th and 7th weeks of gestation and reached estimated optimal level on the 8th and 9th weeks of gestation. In the 9th week of gestation, immunoreactivities specific to CDX1, CDX2 and CDX4 were restricted in epithelium of the midgut. Conclusions: CDX1, CDX2 and CDX4 proteins began to express in human midgut in the 6th week of gestation. From the 6th to 9th week of gastation, the expression of CDX1, CDX2 and CDX4 proteins gradually increase and exhibited overlapping expression patterns, suggesting that CDX genes may be involved in early development of the epithelium of human midgut. Cross-regulatory interactions may exist among CDX genes with respect to human midgut development.